Pulmonary artery compliance: its role in right ventricular-arterial coupling - Fourie, Pieter R; Coetzee, André R; Bolliger, Chris T (Cardiovascular research, 1992)
Objective: The aim was to investigate the ventricular/vascular coupling of the intact right heart under conditions of normal operation and acute pulmonary hypertension. Methods: Right ventricular contractility was obtained by calculating the end systolic pressure-volume relationship (Ees) and the effective pulmonary arterial elastance (Ea), applying the Windkessel parameters of the pulmonary arterial input impedance. Coupling between the ventricle and its load could be determined in terms of Ees and Ea. Acute pulmonary hypertension was induced by injecting glass microspheres into the pulmonary vascular bed until a mean pulmonary arterial pressure of more than 35 mm Hg had been reached. Experimental subjects were Landras/Large white pigs (n=ll), studied under general anaesthesia. Ees was obtained by normalising the right ventricle pressure-diameter equivalent of Ees to stroke volume. The lumped element parameters of the Windkessel analogue were calculated from the pulmonary artery pressure and blood flow. Stroke work was calculated from the pressure-volume loop and oxygen consumption derived from the pressure-volume area. Efficiency was taken to be the ratio between stroke work and oxygen consumption. Results: Ea increased significantly as mean pulmonary artery pressure rose, while Ees remained linear and constant. Stroke work, as well as efficiency, increased, with the maximum of the stroke work curve lying to the right of the efficiency maximum. At the control step (before pulmonary artery hypertension), Ees=1.71 Ea (n=ll). Conclusions: Under control conditions, the right ventricle operates at maximum efficiency and submaximal work output. Compliance of the pulmonary artery is a significant factor in decoupling the right ventricle from its vascular load. As the compliance decreases with acute pulmonary hypertension, the maximum stroke work against load point shifted in such a manner that the right ventricle changed its operational status from a flow to a pressure pump, resulting in a decreased stroke volume. Cardiovascular Research 1992;26:000–000